Chemical and Functional Characteristics of Soy Milk Kefir at Various Doses of Starter and Addition of Telang Flower Juice (Clitoria ternatea L.) - If'all; Sultan Bisinda; Sri Sudewi; Sitti Sabariyah; Ratnawati (Postgraduate, University of Mataram, 2025)
Soy milk kefir offers a plant-based alternative to dairy probiotics. This study aimed to enhance both the chemical and functional characteristics of soy milk kefir by evaluating the effects of varying kefir grain starter doses and added Clitoria ternatea (telang) flower juice. A 3x4 factorial design was employed using three starter levels (40g, 50g, 60g per liter soy milk) and four telang juice concentrations (0ml, 10ml, 20ml, 30ml per liter). Key parameters analyzed post-fermentation included protein content (Kjeldahl), lactic acid (titration), pH, Water Holding Capacity (WHC, centrifugation), anthocyanin content (differential pH method), and Lactic Acid Bacteria (LAB) count (plate count). Results indicated significant (p<0.05) effects of both starter dose and telang juice concentration, and their interaction, on all measured characteristics. Specifically, the 40g starter + 30ml juice treatment yielded the highest protein (39.35%) and anthocyanin (18.42 mg/mL). The 50g starter + 20ml juice treatment showed the highest WHC (67.30%). The 60g starter + 30ml juice treatment produced the highest lactic acid (20.30%). Higher LAB counts were observed in several treatments including A0B0, A1B1, A2B2, and A2B3 compared to others. In conclusion, optimizing kefir grain dosage and adding telang flower juice significantly improves soy milk kefir's nutritional profile (protein) and functional attributes (anthocyanins, WHC, LAB), demonstrating its potential as an enhanced plant-based functional food.